Mamirauá:: conservation that came from the canopy - Franco, José Luiz de Andrade; Santana, Marcelo Ismar (Sustainability in Debate, 2014)
This gallery of photos and the text that accompanies it are the result of a trip made to the Sustainable Development Reserve Mamirauá by the photographer and professor at the University of Brasília (Veterinary Medicine) Marcelo Ismar Santana and by the professor - also at the University of Brasília- (History/Center for Sustainable Development), José Luiz de Andrade Franco. The goal was to learn about and make photographic records of three on-going research projects about primates: the white bald-headed uakari (Cacajao calvus calvus), the blackish squirrel monkey (Saimiri vanzolinii), and the common squirrel monkey (Saimiri sciureus cassiquiarensis). The visit included field trips, deepening the understanding of the actions that are developed in Mamirauá and allowing for a varied set of photographs of landscapes, flora, fauna, riverside communities and the activities of researchers and managers.